Second-order magnetic critical points at finite magnetic fields: Revisiting Arrott plots - Bustingorry, Sebastián (2016)
The so-called Arrott plot, which consists in plotting H/M against M2, with H the applied magnetic field and M the magnetization, is used to extract valuable information in second-order magnetic phase transitions. Besides, it is widely accepted that a negative slope in the Arrott plot is indicative of a first-order magnetic transition. This is known as the Banerjee criterion. In consequence, the zero-field transition temperature T∗ is reported as the characteristic first-order transition temperature. By carefully analyzing the mean-field Landau model used for studying first-order magnetic transitions, we show in this work that T∗ corresponds in fact to a triple point where three first-order lines meet. More importantly, this analysis reveals the existence of two symmetricalsecond-order critical points at finite magnetic field (Tc,±Hc). We then show that a modified Arrott plot can be used to obtain information about these second-order critical points. To support this idea we analyze experimentaldata on La2/3Ca1/3MnO3 and discuss an estimate for the location of the triple point and the second-order critical points